2009
DOI: 10.1152/ajprenal.00298.2009
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the length-active tension relationship in rabbit detrusor

Abstract: Studies have shown that the length-tension (L-T) relationships in airway and vascular smooth muscles are dynamic and can adapt to length changes over a period of time. Our prior studies have shown that the passive L-T relationship in rabbit detrusor smooth muscle (DSM) is also dynamic and that DSM exhibits adjustable passive stiffness (APS) characterized by a passive L-T curve that can shift along the length axis as a function of strain history and activation history. The present study demonstrates that the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 48 publications
(69 reference statements)
2
51
0
Order By: Relevance
“…3,[6][7][8]12,13,19,21,22 However, a model explaining how both L-T curves can shift simultaneously has not been developed because L-T a and L-T p curves are thought to be caused by structurally distinct molecules in spatially distinct locations. This study builds upon our recent work which identified adaptation of the L-T a relationship in bladder 24 and our previous work characterizing the L-T p relationship in bladder. [25][26][27] Our previous studies showed that the L-T p relationship in rabbit DSM is dynamic and that DSM exhibits adjustable passive stiffness characterized by an L-T p curve that can shift along the length axis as a function of strain history and activation history.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…3,[6][7][8]12,13,19,21,22 However, a model explaining how both L-T curves can shift simultaneously has not been developed because L-T a and L-T p curves are thought to be caused by structurally distinct molecules in spatially distinct locations. This study builds upon our recent work which identified adaptation of the L-T a relationship in bladder 24 and our previous work characterizing the L-T p relationship in bladder. [25][26][27] Our previous studies showed that the L-T p relationship in rabbit DSM is dynamic and that DSM exhibits adjustable passive stiffness characterized by an L-T p curve that can shift along the length axis as a function of strain history and activation history.…”
Section: Introductionmentioning
confidence: 77%
“…Together, our previous studies demonstrate that both APS and length adaptation of the L-T a curve each impact the maximum total tension observed at a particular DSM length. 24,26 What remains to be determined regarding the role of length adaptation on the L-T relationships in DSM includes (1) whether adaptation at one particular muscle length shifts the entire L-T a curve, as has been suggested to occur in ASM; 31 (2) whether adaptation from a longer to a shorter length is different from adaptation from a shorter to a longer length; and (3) the relationship between adaptation of the L-T a and L-T p curves. Answering these questions will provide important insight into the role of length adaptation in DSM.…”
Section: Introductionmentioning
confidence: 99%
“…Because muscle cell active tension is due to the transmission through cytoskeletal adhesion junctions of tension generated by actomyosin cross bridges, the proposed mechanisms for length adaptation of active tension include changes in actin and myosin polymerization leading to addition and subtraction of sarcomeres, and sarcomere and cytoskeletal adhesion junction reorganization (13,16,17,25). Although the most extensive work on length adaptation of active tension has been done on airway smooth muscle (12), there is also evidence of length adaptation of active tension in certain arteries (40,51), rabbit bladder (45), and cat ileum (3).…”
mentioning
confidence: 99%
“…The concept that the tension-generating capacity of SMCs is a steep function of diameter has been acknowledged for many decades. The notion that this active strain-tension relation is malleable is well appreciated for airway and bladder SMCs [43,44,45], while recent work also demonstrates such plasticity in small arteries. We previously demonstrated contractile plasticity in mesenteric arteries exposed to flow restriction in vivo [11] or following overnight incubation with ET-1 [10].…”
Section: Discussionmentioning
confidence: 99%